Analysis of goal scoring patterns in Japan Women's Football League Division 1: Comparison between top ranked teams and middle to low ranked teams - Yamakoshi, S. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
The aim of this study was to examine differences in goal scoring patterns between top ranked teams and middle to low ranked teams in 20xx Japan Women's Football League Division 1. Goals from open play were analyzed in terms of (1) the number of touches the goal scorer needed in order to take a shot, and the area of the shots that led to the goal, (2) actions prior to the goal, and their location, (3) the location of ball recovery, and the number of passes as well as the time after recovering the ball to scoring the goals. Chi- squared test or t-test was performed to examine the differences in goal scoring patterns between top ranked teams and middle to low ranked teams. The results showed that top ranked teams scored significantly (1) more goals by shots requiring 2 or more touches, fewer goals by shots requiring 1 touch, and also more goals from outside the penalty area and fewer goals from inside the penalty area, (2) more goals after a through pass and dribbling, and fewer goals after crossing and a rebound, (3) more goals from possessions started in the defensive third, requiring a significantly greater number of passes, and requiring a longer time after recovering the ball until scoring the goal. These results might reflect differences in the qualities of players and the use of attacking strategies between top ranked teams and middle to low ranked teams.